Anthropometric variables and body composition and SEMG frequency of the spine rectifier in children with scoliosis and scoliotic posture - Wilczyński, Jacek; Karolak, Przemysław; Janecka, Sylwia (Journal of Education, Health and Sport, 2018)
The purpose of the research was the analysis of the relationship between the anthropometric variables and body composition and frequency of SEMG rectifier of the spine in children with scoliosis and scoliotic attitude. Backbone has been examined by optoelectronic Diers formetric III 4 d. The method photogrammetric video recording of back surface through a process image stereography. Body composition was determined by using the TANITA body composition Analyzer MC 780 m. Analysis of the electromyographical of the spine extensors was performed with the help of 12 channel camera Noraxon TeleMyo DTS. Spine examination method Diers formetric III 4 d has shown in 103 (41%) of children scoliosis. The attitude of scoliotic diagnosed with 141 (56.17%) children. With the correct attitude was 7 (3.0%) children. The most important and significant statistically predictors for model’s anthropometric variables, body composition and the frequency of the charger back test in different positions within the Group of scoliosis were the variables BMI (p = 0.01) and percent fat (%) (p = 0.03). Variance explained by the independent variables in the model adopted is 40% of the total variation (R ^ 2 = 0.40), indicating a small adjustment to the data, however, anticipated the level of statistical significance (p = 0.001) have been met, and also received good the value of the test statistic F = 3.33. In the group the basics of scoliotic the mass of fat (p = 0.01). The model was explained only in 26% (R ^ 2 = 0.26), which is low, but anticipated the level of statistical significance (p = 0.01) was also met, and also received the appropriate statistical test value F = 5.10. She has a substantial dependency between certain variables to the anthropometric and body composition and frequency of SEMG rectifier of the spine in children with scoliosis and scoliotic attitude.